Energy storage devices for renewable energy-based systems : rechargeable batteries and supercapacitors - Kularatna, Nihal; Gunawardane, Kosala (Academic Press, 2021)
Energy Storage Devices for Renewable Energy-Based Systems: Rechargeable Batteries and Supercapacitors, Second Edition is a fully revised edition of this comprehensive overview of the concepts, principles and practical knowledge on energy storage devices. The book gives readers the opportunity to expand their knowledge of innovative supercapacitor applications, comparing them to other commonly used energy storage devices. With new application case studies and definitions, this resource will strengthen your understanding of energy storage from a practical, applications-based point-of-view without requiring detailed examination of underlying electrochemical equations. Users will learn about various design approaches and real-time applications of ESDs. Electronic engineering experts and system designers will find this book useful to deepen their understanding on the application of electronic storage devices, circuit topologies, and industrial device data sheets to develop new applications. The book is also intended to be used as a textbook for masters and doctoral students who want to enhance their knowledge and understanding the concepts of renewable energy sources and state-of-the-art ESDs. Provides explanations of the latest energy storage devices in a practical applications-based context Includes examples of circuit designs that optimize the use of supercapacitors Highlights the unique benefits of these devices